The Development of Strategies to Increase the Productivity of Fisheries Agro-industry Based on Halal Product Assurance System Using Failure Mode Effect Analysis (FMEA) - Wahyuni, Hana Catur; Handayani, Puspita (Department of Agro-industrial Technology, University of Brawijaya, 2023)
AbstractIndonesian food products need to comply with halal regulations, including the ones from fisheries-based agro-industry. The absence of halal certificates will limit the market and consequently will lead to the risk of lower productivity performance. This study aims to identify sources of risk in the fisheries agro-industry based on Indonesia’s Halal Assurance System called Sistem Jaminan Produk Halal (SJPH). It conducts risk assessments and develops strategies to increase the productivity performance of the industry based on the identified risks. The criteria considered in the risk identification including commitment and responsibility, raw material, production process, final product as well as monitoring and evaluation. The research used Failure Mode Effect Analysis (FMEA). The data was collected through observation, interviews, and questionnaires. All identified risks were then evaluated and eliminated based on the Risk Priority Number (RPN). The research was conducted on ten fisheries-based agro-industries in the Sidoarjo Regency, East Java, Indonesia. The study shows that there are 22 sources of risk, with the highest-ranked one is training activity. The recommended strategy to increase the halal-based productivity performance is strengthening the commitment of all involved stakeholders, increasing human resources' knowledge, improving facilities and infrastructure as well as strengthening monitoring and evaluation using management information systems.Keywords: FMEA, halal, risk management, SJPH AbstrakProduk pangan di Indonesia perlu memenuhi ketentuan halal, termasuk produk agroindustri perikanan. Ketiadaan sertifikat halal akan menyebabkan terbatasnya cakupan wilayah pemasaran dan berdampak pada risiko penurunan produktivitas. Penelitian ini bertujuan untuk mengidentifikasi sumber risiko di agroindustri perikanan berdasarkan Sistem Jaminan Produk Halal (SJPH), melakukan penilaian risiko, dan mengembangkan strategi untuk meningkatkan produktivitas berdasarkan risiko tersebut. Kriteria penentuan risiko adalah komitmen, bahan, proses produksi halal, produk, serta monitoring dan evaluasi. Metode penelitian menggunakan Failure Mode Effect Analysis (FMEA) dengan metode pengumpulan data melalui observasi, wawancara, dan kuesioner. Eliminasi risiko selanjutnya dilakukan berdasarkan peringkat Risk Priority Number (RPN). Penelitian dilakukan pada sepuluh usaha agroindustri perikanan di Kabupaten Sidoarjo, Jawa Timur. Hasil penelitian menunjukkan bahwa terdapat 22 sumber risiko, dengan risiko tertinggi pada kegiatan pelatihan, sehingga pihak yang terlibat dalam proses produksi halal tidak memahami ketentuan yang berlaku. Strategi peningkatan produktivitas berbasis risiko halal adalah penguatan komitmen pelaku usaha, peningkatan pengetahuan sumber daya manusia, peningkatan sarana dan prasarana, serta penguatan pemantauan dan evaluasi melalui pemanfaatan sistem informasi manajemen.Keyword: FMEA, halal, manajemen risiko, SJPH